Elastic-plastic stress investigation on two interacting cracks - Han, Jin Xuan (Nanyang Technological University, 2020)
There are many engineering disasters happened in the past and present society and it had cost us several human lives, resources and money. It was found out that most of the engineering disasters are closely related to structural failure which were caused by unforeseeable external or environmental effects such as extreme weather or during the design and construction phase. Crack is one of the main reasons why it is hard for the experts to design against fracture. It is because of the presence of cracks in a structure, it modifies and alter the local stresses around the crack tip area to an extent that the elastic stress analyses done by experts are not enough. This cause a huge problem as cracks are present in all structures and they can propagate catastrophically with little warning. Thus, this report aims to find out how two cracks will interact with each other under a constant pressure force. Various parameters such as the distance, angle and length ratio between the two cracks are changed to see their behavior. The author will be using ANSYS Mechanical APDL software to carry out various simulation and obtaining the stress intensity factor for both cracks. This software is one of the common Computer Aided Engineering software which uses finite element method to obtain various simulation results. The results show that both cracks generally show lesser interaction when the distance, angle and length ratio between them increases which were further explained in the following report. Future work is also suggested for more comprehensive studies of the interaction and behavior of two cracks.